Encyclopedia of Engineering - Barretta, Raffaele; Agarwal, Ramesh; Żur, Krzysztof; Ruta, Giuseppe (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Encyclopedia of Engineering aims at providing a collection of entries concerning several fields of Engineering Sciences. The reprint provides a historical overview, starting from the investigation of Mechanics and Science in Ancient Greece and showing their evolution over time. The topical collection focuses on Civil, Mechanical and Aerospace Engineering providing basic concepts as well as novel trends in modeling, design and construction of engineering systems, structures, and materials. Special attention is also given to the recent developments and achievements in the framework of Nanoscience and Nanotechnology.